Diabetes-related distress and psychological burden in patients with type 1 and type 2 diabetes – the role of child maltreatment, personality functioning, and epistemic trust: findings from a German clinical inpatient sample - Zara, Sandra; Ullrich, Imogen Carla; Leveling, Anna Maria; Saretzki, Friederike Gisela Genoveva; Schmitz, Jana; Eckhard, Michael; Kruse, Johannes; Kampling, Hanna (Frontiers in Psychiatry, 2025)
IntroductionPatients with diabetes exhibit high frequencies of psychological burden and diabetes-related distress. Child maltreatment has been independently linked to both diabetes and psychological burden. We aimed 1) to explore the association between child maltreatment and diabetes-related distress, and between child maltreatment and psychological burden, and 2) to investigate the mediating role of personality functioning (psychological abilities with regard to the self and others) in this association. We included epistemic trust (openness for social learning) and its impairments mistrust (the tendency to consider information sources as unreliable or ill-intended) and credulity (lack of vigilance and discrimination between trustworthy and untrustworthy information) as covariates.MethodsIn a sample of n=119 patients with type 1 or 2 diabetes aged 18-69, self-report questionnaires assessed diabetes-related distress (PAID-5), psychological burden (PHQ-D, PHQ-9, PHQ-15), child maltreatment (CTQ), personality functioning (OPD-SQS), and epistemic trust, mistrust, and credulity (ETMCQ). Mediation analyses assessed the role of personality functioning in the association between child maltreatment, diabetes-related distress, and psychological burden, including epistemic trust, mistrust, and credulity as covariates.ResultsPatients with child maltreatment compared to those without showed higher diabetes-related distress (t(112)=4.033, p<.001, d=.756) and higher frequencies of major depressive syndrome (χ2(1)=10.968, p<.001, φ=.310) with medium effect sizes. They showed higher frequencies of somatoform syndrome (χ2(1)=8.130, p=.004, φ=.267), panic syndrome (χ2(1)=6.281, p=.012, φ=.235), and other anxiety syndromes (χ2(1)=8.828, p=.003, φ=.278), with small effect sizes. Impairments in personality functioning were more severe (t(100,857)=5.136, p<.001, d=.967), with a large effect size. Epistemic mistrust and credulity were significantly higher (mistrust: t(111)=3.677, p<.001, d=.692; credulity: t(111)=5.000, p<.001, d=.941), with medium and large effect sizes. No differences regarding epistemic trust were found (t(111)=.409, p=.683, d=.077), with the effect size below the threshold for small effects. Personality functioning mediated the association between child maltreatment and diabetes-related distress (b=.03, 95%-CI [.005,.053]), depressive symptoms (b=.08, 95%-CI [.030,.129]), and somatic symptoms (b=.06, 95%-CI [.020,.122]).ConclusionsIn a clinical diabetes sample, diabetes-related distress and psychological burden are frequently reported, and personality functioning is impaired, particularly after child maltreatment. Addressing these impairments and initiating psychosomatic treatment including psychodynamic or mentalization-based interventions might offer new clinical treatment avenues.